2016
DOI: 10.5812/ijp.7695
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Prophylaxis and Treatment of Urinary Tract Infections in Children

Abstract: Context: Urinary tract infection (UTI) is a common and important problem during childhood that may cause chronic morbidities. Live beneficial microorganisms called probiotics have been investigated for their use in the prophylaxis and treatment of UTIs in children. Evidence Acquisition: We aimed to discuss data about use, mechanisms and effects of probiotics on pediatric UTIs. We searched the literature, including PubMed, Medline and Cochrane databases from January 2001 to May 2016, and limited the search to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Newborns randomly assigned received either 1 Â 10 9 [CFU] of L. acidophilus boucardi strain or multispecies probiotic which contains 1 Both probiotics in powder presentation form were mixed in the feed each 24 h during three weeks and no color/odor of the milk given to the infants changed. Nurses who were blinded to the group assignment individually prepared fresh supplement suspensions.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborns randomly assigned received either 1 Â 10 9 [CFU] of L. acidophilus boucardi strain or multispecies probiotic which contains 1 Both probiotics in powder presentation form were mixed in the feed each 24 h during three weeks and no color/odor of the milk given to the infants changed. Nurses who were blinded to the group assignment individually prepared fresh supplement suspensions.…”
Section: Interventionmentioning
confidence: 99%
“…6,7 Furthermore, probiotics have been widely studied in infants; for example, a recent study suggests that probiotics may be beneficial as an adjunct treatment for term infants with hyperbilirubinemia by reducing the duration of hospitalization, 8 and in the prophylaxis and treatment of urinary tract infections in children. 9 The lower prevalence of protective Lactobacillus or Bifidobacterium species in preterm infants compared to term infants makes these species of probiotics a target for the prevention of NEC. 10 A systematic review to assess the efficacy and safety of probiotics for the prevention of NEC in preterm infants found that severe NEC was significantly reduced in trials where patients received probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocins have been isolated from a variety of microbiomes, demonstrating antimicrobial activity against clinically relevant pathogens. Bacteriocins have been used to target pathogens both in vitro [ 45 - 47 , 54 , 62 ] and in vivo [ 48 , 63 ] , exerting probiotic effects [ 49 , 64 ] , inhibiting biofilm formation [ 60 ] , and resensitising resistant bacterial strains to antibiotics [ 65 ] , while demonstrating limited cytotoxic effects on the commensal healthy microbiomes. It is hoped that the identification of bacteriocins from untapped niches such as the urobiome can aid in the transition into use in clinical settings to control infections.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, LAB bacteriocins have shown promise in inhibiting human pathogens in both in vitro studies against Pseudomonas aeruginosa [45] , uropathogenic E.coli [46] , and Candida spp. [47] and in in vivo studies against Gardnerella vaginalis [48] , and in trials using bacteriocin-producing probiotics against bacterial vaginosis and UTIs [49] . Novel variants of these bacteriocins can aid in the treatment/prevention of infections, further highlighting the importance of in silico screening studies.…”
Section: Analysis Of Selected Novel Pbgcs Identified Among Lactobacil...mentioning
confidence: 99%
“…Огляд літератури з Pubmed, Medline і бази даних Cochrane за 2001-2016 роки підтверджує доцільність застосу-вання пробіотиків у профілактиці та комплексному лікуванні інфекцій сечових шляхів у дітей. Доведена здатність певних пробіотичних культур пригнічува-ти уропатогени шляхом конкуренції за рецептори й поживні речовини, прямого знищення, імунної модуляції та інгібування метаболітів [7]. Одним з можливих механізмів дії пробіотиків у запобіганні інфекціям сечових шляхів та розвитку рецидивів є інгібування утворення уропатогенами біоплівок [7][8][9][10].…”
Section: вступunclassified